2023
DOI: 10.1021/jacs.2c13890
|View full text |Cite
|
Sign up to set email alerts
|

6,6′-Biindeno[1,2-b]anthracene: An Open-Shell Biaryl with High Diradical Character

Abstract: We report in situ generation of a 6,6′-biindeno [1,2-b]anthracene (BIA) derivative as an open-shell biaryl with high diradical character, which could be identified by mass spectrometry, NMR spectroscopy, single-crystal X-ray analysis, UV−vis−NIR absorption spectroscopy, and electron paramagnetic resonance (EPR) spectroscopy. Theoretical calculations by various methods and variable-temperature EPR analyses were performed to tackle the elusive ground state of BIA diradical, suggesting a singlet ground state with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Initially, at room temperature, the characteristic half-field transition of Δ m s = ±2 was not detected in these compounds. This observation aligns with behaviors seen in other disjointed main-group biradicals, characterized by large interspin distances and minimal zero-field splitting (ZFS) parameters . In such cases, the half-field transition intensity inversely correlates with the sixth power of the interspin distance ( I (Δ m s = ±2) ∝ r –6 ).…”
Section: Resultssupporting
confidence: 90%
“…Initially, at room temperature, the characteristic half-field transition of Δ m s = ±2 was not detected in these compounds. This observation aligns with behaviors seen in other disjointed main-group biradicals, characterized by large interspin distances and minimal zero-field splitting (ZFS) parameters . In such cases, the half-field transition intensity inversely correlates with the sixth power of the interspin distance ( I (Δ m s = ±2) ∝ r –6 ).…”
Section: Resultssupporting
confidence: 90%
“…The paramagnetic nature of 4 was confirmed by solution and solid-state EPR spectroscopy (Figure ). In THF, the EPR spectrum of 4 displays a single broad signal centered at g = 2.004, with no observable hyperfine splitting, in agreement with EPR spectra observed for carbon-based PAH biradical systems. ,, The powder EPR spectrum of 4 displays low and high field transitions (Δ m s = ±1) characteristic of organic spin triplets ( S = 1), coinciding with a central transition determined through simulation to be a monoradical ( S = ) impurity originating from a single N– carbene C–B spin system . The assignment of this impurity is consistent with our previously reported CAAC-stabilized borepin and borafluorene radicals, where the spin system is localized to the N– carbene C–B moiety. , The point-dipole approximation employing the simulated zero-field splitting parameter | D′ | (2.62 mT) determined an average interspin distance of 10.2 Å, consistent with crystallographic measurements indicating a distance of approximately 9.57 Å between the centroids of the two N– carbene C–B fragments.…”
Section: Resultssupporting
confidence: 71%
“…Conversion of 1 into diradical 4 leads to a bathochromic shift in absorbance. Compound 4 exhibits low energy absorption features at 520 and 472 nm which resemble the low-lying singlet excited states typical for singlet biradicaloids and are suggested to originate from a doubly excited electronic configuration …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no sign of isomerization to the folded form (Scheme 29). 115 Furthermore, for the biradical form of 33, both the singlet and triplet states were obtained as energyminimized structures by DFT calculation (CASSCF(12e,12o)/ def2-TZVPP) with the triplet state as a ground state. The VT-ESR study showed that the signal intensity of ΔM s = ±2 increased with a decrease in temperature, thus demonstrating a triplet ground state.…”
Section: Biradical Perpendicular Form Derived From An Extended Anthra...mentioning
confidence: 99%